Right‐sided Bochdalek hernia in an elderly patient: a case review of adult Bochdalek hernias from 1982 to 2015 in Japan - Ohtsuka, Yasuhiro (Acute Med Surg, 2016)
CASE: An 89‐year‐old woman was admitted to our hospital because of dyspnea following abdominal pain and vomiting. According to chest computed tomography findings, a diagnosis of acute respiratory failure due to right‐sided Bochdalek hernia was made. OUTCOME: Emergency laparotomy revealed that a bowel loop from the terminal ileum to the transverse colon had herniated into the right thoracic cavity through the foramen of Bochdalek. The herniated organs were reduced to the abdominal cavity and the foramen was repaired by direct suturing. The patient had good recovery and was discharged 78 days later. CONCLUSION: Bochdalek hernias in elderly patients are rare, but may be complicated by strangulation of the herniated organ. This should be taken into account by acute care physicians. To prevent this fatal complication, regardless of symptoms, surgical treatment may be essential as soon as a diagnosis of adult Bochdalek hernia is made.